Nixon off the Record - Crowley, Monica (New York Random House, 1996)
With fully reconstructed conversations based on extensive notes made at the time, Nixon off the Record puts the reader in the room with the thirty-seventh president, listening to his views on leadership, his opinions of White House predecessors and successors, his activities and thoughts during the 1992 presidential campaign and election, and his assessment of Bill Clinton's first year in office and his potential challengers in 1996. Nixon's views give voters uncommon criteria by which to measure presidential candidates - including Bob Dole - and their ability to exercise effective leadership. Richard Nixon was one of the most controversial and indestructible presidents of the twentieth century. With her privileged perspective and unlimited access to Nixon, Crowley has written a perceptive and spirited memoir that shows not just what Nixon thought in the last years of his life but who he was. She offers an unprecedented behind-the-scenes view of Nixon's activities and opinions, giving the reader a front-row view of recent American political history. Nixon's unparalleled experience placed him in a unique position to judge leaders who had come before and after. His assessments are candid, astonishing, and sometimes explosive. This book places those judgments in context and brings them alive for the last American presidential election of the twentieth century.
Include Index
Keywords: Nixon, Richard M. (Richard Milhous), 1913-1994 -- Political leadership -- Presidents--Election